Дьявольский поезд: [роман] / Наталья Солнцева - Солнцева Наталья Анатольевна (Мистический детектив, 2016)
Экземпляры: (20170926) / Инвентарный номер: 49817 / Цена: 149.00 / Сис.шифр: 84Р7 / Авт.знак: С 60 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44